Referral Criteria from Community Clinics to Pediatric Emergency Departments - Jacob Urkin; Ilan Segal; Nurit Barak; Joseph Press (The Scientific World Journal)
Referral of patients to a pediatric emergency department (PED) should be medically justified and the need for referral well communicated. The objectives of this paper were (1) to create a list of criteria for referral from the community to the PED, (2) to describe how community physicians categorize their need for referral, and (3) to determine agreement between the physician's referral letter and the selected criteria. We present a descriptive study of referrals to the PED of Soroka University Medical Center, Beer-Sheva, Israel, during February to April 2003. A list of 22 criteria for referral was created, using the Delphi method for reaching consensus. One or more criteria could be selected from this list for each referral, by the referring community physicians and, independently, based on the physicians' referral letters, by two consultants, and compared. There were 140 referrals included in the study. A total of 262 criteria for referral were selected by the referring community physicians. The criteria most frequently selected were: “Need for same-day consultation/laboratory/imaging result not available in the community” (32.1%), “Suspected life- or organ-threatening infection” (16.4%), and “Need for hospitalization” (15.7%). Rates of agreement regarding criteria for referral between the referring physicians and the two consultants, and a senior community pediatrician and a senior PED pediatrician, were 57.9 and 48.6%, respectively. We conclude that the standard referral letter does not convey in full the level of need for referral to the PED. A list of criteria for referral could augment efficient utilization of emergency department services and improve communication between community physicians and the PED.